Asian Digital Libraries. Looking Back 10 Years and Forging New Frontiers
DOI: 10.1007/978-3-540-77094-7_38
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Tagging and Accessibility Information Sharing Using a Geospatial Digital Library

Abstract: Mobile tagging is an extension of social tagging that allows users to associate location-sensitive information with physical objects in the real world. This paper presents MoTag, a mobile tagging application that is used to help people with disabilities share up-to-date accessibility information about buildings and other physical structures to help them navigate their environment. MoTag integrates with G-Portal, a geospatial digital library for storing, managing and retrieving tags.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Several researchers agree that usefulness and usability are the most significant concepts for the user-centred evaluation of information services [6,7,17,18]. Thus the OPACIAL evaluation aims to investigate how useful and easy are the new library services.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers agree that usefulness and usability are the most significant concepts for the user-centred evaluation of information services [6,7,17,18]. Thus the OPACIAL evaluation aims to investigate how useful and easy are the new library services.…”
Section: Methodsmentioning
confidence: 99%
“…Further, mobile G-portal [18] is a learning assistant integrated a Web-based geospatial digital library of geography resources that supports collaborative sharing and learning for geography fieldwork [8]. Finally, MoTag [4] is a mobile application that is used to help people with disabilities share up-to-date accessibility information about buildings and other physical structure to help them navigate around their environment. However, these systems generally do not support users' further effort to enrich the content with more information.…”
Section: Related Workmentioning
confidence: 99%
“…Goh et al suggested that services that allow users to assess accessibility of a given point-of-interest (e.g., a store, restaurant) could be useful for people with disabilities [52,68,69]. People with mobility impairments could use the services to identify whether the places are navigable.…”
Section: Accessibility-aware Poi Searchmentioning
confidence: 99%